Present Scenario of Waste Management in India - Das, Pradip Kumar (American International Journal of Social Science Research, 2020)
In India, approach towards waste management is unscientific. Even today, large portion of solid waste is dumped indiscriminately on outskirts of places without any prior treatment leading to groundwater contamination and increase in air pollution. Resource recovery from waste and safe disposal of residual in scientifically designed landfills are grossly neglected. The present system is focused on collection and transportation of largely mixed unsegregated waste for sustainable solid waste management, but the capacity to plan and manage the system and ensure the enforcement of rules is a major challenge. This study analyses current scenario of waste management in India. Besides presenting few mitigation choices to respond to the growing challenge, it also suggests mechanisms for ensuring integrated waste management systems.